The Promises of Postcolonial Utopias: Perspectives from the Global South. (3rd January 2023) - Banerjee, Tridib
Abstract: The notion of 'smart cities', with their ubiquitous linked sharing of data and observation, can be both problematic and simultaneously utopian. Tridib Banerjee, Professor Emeritus of Public Policy at the University of Southern California (USC) where he previously held the James Irvine Chair in Urban and Regional Planning, explores the recent adoption of the concept, particularly in the Global South. Notably, Le Corbusier's modernist city of Chandigarh in India has just been named a smart city. What will this mean for law and order, culture, and urban vitality for its inhabitants in coming years?